High-Temperature Electrochemical Hydrogen Pumps and Separators - P. Pasierb; M. Rekas (International Journal of Electrochemistry)
In this work different methods of hydrogen purification were presented and discussed. Special emphasis was given to electrochemical hydrogen pumps and membranes. The general principle of operation of such devices was shown, and the basic criteria for materials selection were formulated. The experimental part shows the example results concerning the pumping efficiency, demonstrating the possibility of application of high-temperature protonic conductors for the construction of pump or membrane for hydrogen purification.